Removal of a Thrombus from the Sigmoid and Transverse Sinuses with a Rheolytic Thrombectomy Catheter - Scarrow, Alan M. (AJNR Am J Neuroradiol, 1999)
Summary: A rheolytic thrombectomy catheter was used to remove thrombus without thrombolytics from the sigmoid and transverse sinuses of a 34-year-old woman. Using small, high-flow fluid jets and Venturi-effect suction, this catheter allowed mechanical removal of thrombus. This technique may obviate the need for thrombolytic agents and the risks associated with their use.